Older but Not Wiser: the Age-Driven Changes in Neutrophil Responses during Pulmonary Infections - Simmons, Shaunna R. (Infect Immun, 2021)
Elderly individuals are at increased risk of life-threatening pulmonary infections. Neutrophils are a key determinant of the disease course of pathogen-induced pneumonia. Optimal host defense balances initial robust pulmonary neutrophil responses to control pathogen numbers, ultimately followed by the resolution of inflammation to prevent pulmonary damage. Recent evidence suggests that phenotypic and functional heterogeneity in neutrophils impacts host resistance to pulmonary pathogens. Apart from their apparent role in innate immunity, neutrophils also orchestrate subsequent adaptive immune responses during infection. Thus, the outcome of pulmonary infections can be shaped by neutrophils. This review summarizes the age-driven impairment of neutrophil responses and the contribution of these cells to the susceptibility of the elderly to pneumonia. We describe how aging is accompanied by changes in neutrophil recruitment, resolution, and function. We discuss how systemic and local changes alter the neutrophil phenotype in aged hosts. We highlight the gap in knowledge of whether these changes in neutrophils also contribute to the decline in adaptive immunity seen with age. We further detail the factors that drive dysregulated neutrophil responses in the elderly and the pathways that may be targeted to rebalance neutrophil activity and boost host resistance to pulmonary infections.